EFFECT OF THE USE OF WARM WATER COMPRESSES ON THE DECREASE IN PAIN INTENSITY IN THE ELDERLY AT COMMUNITY AREA - WennyIno Ischak, Harliani, Lilin Rosianti, Suryani Manurung, Anna Veronica Pont, Agussalim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The elderly are a high-risk group that experiences health problems characterized by physical, biological, psychological, and social changes caused by the aging process including joint diseases. Joint disease is a degenerative process and causes joint pain. Efforts are to reduce pain through the use of warm water compresses. This study aims to identify the effect of the use of warm water compresses on the decrease in pain intensity in the elderly in the working area of Puskesmas (Public Health Center) Antang RW VI. The research design used is pre-experimental research design with the type of research design used is the design of one group pretest & posttest design,with a sample number of 30 respondents, samples taken using purposive sampling. The criteria of the subject are elderly people who experience pain aged ? 60 years, willing to be respondents, do not take painkillers and do not have dementia. The results showed that the intensity of pain in the elderly changed significantly after the warm water compress with the results of a statistical test paired sample t-test obtained P value 0.000 concluded that there is an influence on the use of warm water compresses to decrease the intensity of pain in the elderly in the work area of Puskesmasantang RW VI. It is recommended to Puskesmas officers to provide information and intervention to the elderly about the therapy of warm water compresses against pain reduction.